Classmate Support and English-Speaking Development in Vocational EFL Classrooms: Students’ Perceptions and Experiences - Dinda Puspita Anjani; Prakasit Sophakul; Him'mawan Adi Nugroho (New Language Dimensions, 2026)
This study investigates vocational high school students’ perceptions of classmate support during English-speaking activities and its role in developing students’ confidence, fluency, and accuracy in speaking English. This qualitative research involved 98 eleventh-grade vocational students in East Java, with nine representative students in in-depth interviews. Data were collected through classroom observations, questionnaires, and semi-structured interviews, and were analysed using the interactive model. The findings show a positive perception of the support provided by classmates. Cognitively, students view the support of their classmates as positive encouragement that helps them continue to develop. Affectively, students feel more comfortable and confident speaking because of emotional encouragement such as applause, praise, and attention from classmates. Conatively, students demonstrate active behaviour such as practicing together, giving positive feedback, and imitating the behaviour of friends who are more confident in speaking English. Moreover, the study reveals that classmate support contributes significantly to the improvement of students’ English-speaking skills. Supportive classmates enhance students’ confidence, promote greater fluency through regular practice, and improve accuracy through constructive peer correction. Overall, classmate support plays an essential role in fostering a collaborative learning environment that supports the development of vocational high school students’ English-speaking skills.